2021
DOI: 10.1055/s-0041-1731447
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Comparative Observational Study of Safety and Efficacy of Topical Ozone Gas Therapy in Healing of Diabetic Foot Ulcers versus Only Conventional Wound Management

Abstract: The prevalence of diabetic foot ulcers (DFUs) in India is 11.6%. DFU accounts for major cost expenditure, morbidity, and mortality.1 Ozone gas has antimicrobial and antioxidant properties. We studied efficacy of topical ozone gas therapy in promoting healing of DFU. This is an observational comparative cohort study, n = 160, There were two groups of patients namely: those who received Conventional wound management alone C and those who received topical ozone therapy in addition to conventional wound management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 16 publications
(22 reference statements)
1
14
1
1
Order By: Relevance
“…Te mean healing time was 69.44 ± 36.05 days (range 15-180 days) [32]. Te previous observations are also consistent with the results of the studies by Dhamnaskar et al [33].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Te mean healing time was 69.44 ± 36.05 days (range 15-180 days) [32]. Te previous observations are also consistent with the results of the studies by Dhamnaskar et al [33].…”
Section: Discussionsupporting
confidence: 89%
“…In turn Dhamnaskar S. et al reported that topical ozone gas therapy causes indirectly decrease of overall costs of treatment of patients with DFU as compared to the conventional management, mainly due to the faster rate of ulcer healing and early microbial negativity, resulting in reduction of duration of hospital stay and reduction in requirement of revision surgery [33].…”
Section: Discussionmentioning
confidence: 99%
“…In some ulcers, especially those of vascular origin, the above treatment would be accompanied by the noninvasive application of ozone, as has been done in other studies. 21 If the wound is healing well, cures are scheduled approximately every 2 days until complete healing, or until voluntary discharge, Note: Percentages in relation to the total of the respective column.…”
Section: Wound Treatmentmentioning
confidence: 99%
“…Ozone therapy has been widely used in more than 50 pathological processes, including skin diseases, intervertebral disc herniation, 4 diabetic complications, 5 oral mucosal diseases, cardiovascular and cerebrovascular diseases, 6 and cancer. In terms of skin diseases, topical ozone therapy can be employed to treat infectious skin diseases (e.g., tinea capitis and herpes zoster), 7,8 inflammatory skin diseases (e.g., eczema, psoriasis, atopic dermatitis, and contact dermatitis), 9‐11 autoimmune‐related skin diseases (e.g., pemphigus, bullous pemphigoid, and dermatomyositis) 12,13 and chronic ulcers (e.g., diabetic foot and pressure ulcers) 14,15 . In addition, ozone therapy can be used to clean burns and scald wounds, 16 accelerate wound healing, 17 and promote skin repair after laser cosmetology.…”
Section: Introductionmentioning
confidence: 99%